1995
DOI: 10.1300/j070v03n04_05
|View full text |Cite
|
Sign up to set email alerts
|

Behavior Problems of Sexually Abused Children in Foster Care

Abstract: Research has shown that sexually abused children display a number of behavior problems. Many of these children are placed in substitute care, espec~ally foster homes. The current project was undertaken to measure foster parents' perceptions about the behavior problems of sexually abused children in Iheir care. Two studies were completed. The fust was a large s w e y of foster parents in a Midwestern state. The second study utilized a sample of foster

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 3 publications
1
10
0
1
Order By: Relevance
“…Finally, females and Whites are more likely to experience higher levels of sexual victimization whereas running away more often is positively linked to being a victim of physical assault. With the exception of sexual abuse, these results are in the expected direction and are generally consistent with the larger literature on foster care youth (Benedict et al 1994; Clausen et al 1998; Courtney and Terao 2005; Poertner et al 1999; Taussig 2002; Thompson et al 1994; Unrau and Grinnell 2005; Vaughn et al 2007). …”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Finally, females and Whites are more likely to experience higher levels of sexual victimization whereas running away more often is positively linked to being a victim of physical assault. With the exception of sexual abuse, these results are in the expected direction and are generally consistent with the larger literature on foster care youth (Benedict et al 1994; Clausen et al 1998; Courtney and Terao 2005; Poertner et al 1999; Taussig 2002; Thompson et al 1994; Unrau and Grinnell 2005; Vaughn et al 2007). …”
Section: Discussionsupporting
confidence: 86%
“…Many foster youth have experienced abuse and/or neglect in their family of origin or while in foster care or both (Benedict et al 1994; Clausen et al 1998; Poertner et al 1999; Thompson et al 1994). For example, Lau et al (2003) in their study of high risk youth in the public sector of care found that more than one half of respondents reported at least one type of moderate abuse.…”
Section: Introductionmentioning
confidence: 99%
“…In a large (n = 300) survey of foster parent experiences of behavior problems among sexually abused children in foster care, 77% of carers reported that such children display eating problems either sometimes or frequently, and 23% felt 'bothered' by these problems (Thompson, Authier, & Ruma, 1994). Two studies have described children in foster care who are chronic excessive eaters (hyperphagia), but who are neither obese nor growth impaired (Ayoob, Kaminer, & Zawel, 1994;Demb, 1991).…”
mentioning
confidence: 99%
“…La victimisation sexuelle antérieure est clairement un des facteurs les plus documentés dans les écrits (Gagnon, Tremblay et Bégin, 2005a). Bien que les taux varient considérablement d'une étude à l'autre (de 48 % à 100 %) en ce qui concerne la présence d'une expérience d'agression sexuelle antérieure chez les enfants présentant des comportements sexuels problématiques (Gagnon, Tremblay et Bégin, 2005a), plusieurs auteurs considèrent qu'il s'agit d'un facteur souvent lié au problème (Berliner, 1991;Friedrich, 1993;Thompson, Authier et Ruma, 1994;Bentovim, 2002;Ryan, 2002). Il y a déjà vingt ans, Johnson (1988;1989) identifiait cette caractéristique chez les enfants présentant cette forme de comportements.…”
Section: Problématique Des Enfants Manifestant Des Comportements Sexuunclassified